Evaluating a community academic partnership to advance equity-focused cancer genetic implementation research: a qualitative analysis of partner perspectives - Ariana Naaseh; Meera Muthukrishnan; Isabel Temosihue; Erin L. Linnenbringer (Frontiers in Public Health)
BackgroundForming community academic partnerships (CAPs) can increase the applicability, translation, and dissemination of implementation research focused on addressing health inequities within the community setting. We aimed to explore community and academic partners’ perspectives on their participation in a novel, multi-disciplinary cancer genetic equity CAP focused on developing a multi-level intervention for breast, ovarian, prostate, and pancreas cancers.MethodsWe conducted semi-structured interviews with CAP members. Questions addressed partners’ motivations for participation in the CAP, feedback about the partnership, and opportunities for future CAPs. All interviews were audio-recorded, de-identified, transcribed, and then coded inductively by 2 analysts to identify relevant themes.Results8 CAP members participated. We identified four main themes including motivations to participate and continue engagement in the CAP, perceived CAP successes, perceived CAP challenges, and suggestions and opportunities for improvement. Participants described a variety of motivations, including learning more about cancer genetics and helping patients and communities. Participants valued the multi-disciplinary collaboration and having facilitated partnership discussions. Challenges included ambiguity of expectations for roles and differing perspectives between providers and community members, sometimes leading to frustrations in discussing solutions to potential barriers. Participants described several suggestions for improving future partnerships, such as more clearly defining expectations for participant roles, being able to create a strong vision and targeted approach, bringing their counterparts into clinical and community spaces to better share differing perspectives, and involving leadership stakeholders in the partnership to help address healthcare system barriers.DiscussionOverall, community and academic members were motivated to participate and engage in a CAP to improve cancer genetic equity.